2008
DOI: 10.1111/j.1349-7006.2007.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns in the frequency of Hodgkin lymphoma subtypes and Epstein–Barr virus association in Taiwan

Abstract: Epstein-Barr virus (EBV) infection is a risk factor for Hodgkin lymphoma (HL).To test whether the frequency of HL subtypes and their association with EBV has shifted with rising socioeconomic status in Taiwan, we compared the pathological features and EBV status, detected by in situ hybridization, of HL diagnosed between 1996 and 2007 (99 cases) and 1982 and 1995 (74 cases). The male-tofemale ratio was 121:52 (2.3:1) and the mean age at presentation was 41.5 years. The overall EBV positivity rate was 50% (86/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
6
24
1
1
Order By: Relevance
“…The low proportion of HL in our study (4.1% of total lymphoid neoplasms) was also in good agreement with previous results from Asian countries [1,2,6,9,[13][14][15][16][17][18][19][20][21]23,[25][26][27][28][29][30][31][32][33][34][35][36]38,45,46]. Although the proportion of overall HL was low, subtype distribution showed similar pattern to previous studies from various regions, with nodular sclerosis and mixed cellularity being the common subtypes (Supplementary Table III).…”
Section: Discussionsupporting
confidence: 92%
“…The low proportion of HL in our study (4.1% of total lymphoid neoplasms) was also in good agreement with previous results from Asian countries [1,2,6,9,[13][14][15][16][17][18][19][20][21]23,[25][26][27][28][29][30][31][32][33][34][35][36]38,45,46]. Although the proportion of overall HL was low, subtype distribution showed similar pattern to previous studies from various regions, with nodular sclerosis and mixed cellularity being the common subtypes (Supplementary Table III).…”
Section: Discussionsupporting
confidence: 92%
“…-Middle East (including Tunisia) [4][5][6][7][8][9][10][11][12]: between 28% of cases in a series from Jordan [12] and 70% of cases from Tunisia [4] were EBV-positive with HL; for Egypt [8], 50% were positive and 67% were of the NS type, which is similar to our findings -East Africa [13][14][15][16]: between 44% and 92% of cases were positive in Kenya -Central and South America [17][18][19][20][21][22][23]: between 31% of cases in Argentina [23] and 84% of cases in Peru [17] were positive -Asia [14,[24][25][26][27][28][29][30]: between 39% of cases in China [30] and 82% of cases in India [24] were positive, and the percentage of positive cases in most other countries was high (50% to 69%). For each country, the first column shows the number (n°) of cases studied whereas the other columns show the percentages of positive cases.…”
Section: Discussionsupporting
confidence: 87%
“…[14,20] Unexpectedly however, HD cases in our current study did not show the usual clear bimodal age pattern although the mean age of 26 years was concordant with that reported in a previous Ugandan study. [34] Apparently, the mean age in our series and the Ugandan study indicate that East African HD presents at a considerably younger age than that reported in USA (≈33 years) and Taiwan (41.5 years) [13,34,35] The reasons for the differences are not clear although these may include age-related oncogenic factors, geographical and other environmental factors as well as the influence of HIV infection in sub-Saharan Africa, considering the above-stated proportion of HIV infected HD patients at MNH in our current study. [24] Reports show that childhood HD occurs at a younger age in various countries with limited resources than in western countries.…”
Section: Discussionmentioning
confidence: 48%